Intradialytic Massage as the Evidence Based Nursing to Reduce Leg Cramps in Patients with Chronic Kidney Failure - Putri Nurfitriani; Beti Kristinawati; Haris Joko Prasetyo (Poltekkes Kemenkes Semarang, 2020)
Background: Hemodialysis is a treatment that is often used in patients with chronic kidney failure. However, hemodialysis can cause side effects on its users. One of them is muscle cramps. Muscle cramps are one of the side effects that occur in patients with chronic kidney failure who do hemodialysis.Purpose: To apply the application of intradialytic massage in reducing muscle cramps in patients with chronic kidney failure undergoing hemodialysisMethods: This application was carried out on 7 participants who were selected according to the characteristics of the participants who had been determined. This forward method is in the form of pre-post design with the instrument used, namely FACES wong baker to assess leg cramps.Results: Based on the results of the application of evidence-based nursing, there is a decrease in pain scale after an intradialytic massage.Conclusion: Intradialytic massage can provide benefits in reducing leg cramping pain in kidney failure patients undergoing hemodialysis.